Assessing and mapping energy biomass distribution using a UAV in Finland - Lopatin, Evgeny; Lopatina, Anna (Taylor & Francis, 2017)
The increasing need to reduce greenhouse gas emissions to slow down climate change requires more effective and versatile methods for producing energy. In Finland, common reed and forest biomass are used for energy production. There are efforts to increase the utilisation of renewable energy resources. The potential intensification of renewables utilisation may result in changes to the landscape's structure and functions. The objective of this study was to develop a method for energy biomass mapping in landscapes using high-resolution remote sensing data from an unmanned aerial vehicle (UAV). The images were obtained from UAVs in Ojalahti, Lipperi, Finland, and a point cloud was calculated from the overlapped images. Individual plants were automatically identified using object-oriented image processing. The size of the individual plants was measured from orthophotographs and the point cloud. It was possible to develop an accurate three-dimensional model of the biomass distribution within the landscape. The error in height measurements of common reed plants and forest trees was 0.044 m. The root-mean-square deviation in common reed biomass measurements using the UAV data obtained was 0.096 m3. The new method developed in this study could be used as a cost-effective solution for common reed biomass resources assessment. This would allow for the mobilisation of common reed biomass for sustainable energy production.
Keywords: UAV; Common reed; biomassa; mittausmenetelmät; Biomass; Assessment; järviruoko